Learning from Regional Successes: Strengthening Afghanistan's Pharmaceutical Supply Chain through the Experiences of Pakistan, Iran, and India - Saleh, Mohammad Yusuf; Azimi, Hamdullah (PT. Riset Press International, 2025)
This research examines the challenges confronting Afghanistan's pharmaceutical supply chain management (PSCM) in the aftermath of prolonged conflict, with an emphasis on enhancing access to essential medicines. The Afghan pharmaceutical sector is characterized by systemic inefficiencies, regulatory shortcomings, inadequate infrastructure, and disruptions stemming from years of instability. Drawing insights from the experiences of neighboring countries—Pakistan, Iran, and India—that have navigated similar obstacles, this study identifies strategic interventions to fortify Afghanistan’s PSCM. This research follows a qualitative method and a deductive approach. Key recommendations include strengthening regulatory frameworks to ensure the quality and safety of pharmaceuticals, leveraging digital technologies for improved inventory and distribution management, and enhancing cold chain infrastructure for temperature-sensitive products. The role of centralized procurement systems and public-private partnerships (PPPs) is underscored as vital for increasing efficiency and reducing costs. Furthermore, fostering local pharmaceutical manufacturing is proposed as a crucial step toward self-sufficiency and resilience. By adapting successful strategies from its neighbors to its distinct context, Afghanistan can develop a more robust, transparent, and sustainable pharmaceutical supply chain, ultimately improving public health outcomes and ensuring consistent access to life-saving medications.